Laminar burning velocities of n-decane and binary kerosene surrogate mixture. (1st January 2017) - Alekseev, V.A.; Soloviova-Sokolova, J.V.; Matveev, S.S.; Chechet, I.V.; Matveev, S.G.; Konnov, A.A.
Abstract: Laminar burning velocities of n -decane and binary kerosene surrogate mixture consisting of n -decane (80%) and benzene (20%) by liquid volume were determined at atmospheric pressure and initial gas temperatures of 338 and 358 K. The heat flux method was employed to measure the burning velocity in non-stretched flames and three kinetic mechanisms were used to simulate the results: JetSurF 2.0, and two models for kerosene developed at Politecnico di Milano: Skeletal Surrogate (121 species) and high-temperature detailed (ver. 1412). New measurements were compared with available literature results at 400 K by extrapolation, which was performed using calculated temperature dependence of the laminar burning velocity. The data determined with the heat flux method agree with some previous counterflow burner measurements and disagree with the data from spherical flames. The detailed mechanism from PoliMi was able to reproduce the present experiments the best. The increase of the burning velocity in the surrogate mixture compared to n -decane was found to be insignificant.